S-TOFHLA in mild Alzheimer's disease and Mild Cognitive Impairment patients as a measure of functional literacy: Preliminary study - Maira Okada de Oliveira; Cláudia Sellitto Porto; Sonia Maria Dozzi Brucki (Dementia & Neuropsychologia)
Abstract The greatest difficulty in diagnosing cognitive loss in our population is the diversity of its education which has a broad spectrum ranging from illiteracy, functional illiteracy and different degrees of literacy, even in those with the same level of schooling. Objectives: To verify whether there is impairment on the S-TOFHLA among individuals with AD and MCI compared with healthy controls, and to compare performance on the S-TOFHLA performance with neuropsychological tests and the scores achieved on the Raven's Colored Matrices and Vocabulary and Block Design (WAIS-III) as a measure of estimated intellectual level. Methods: 59 subjects: controls (n=23; age 70.96±8.31y; schooling 10.2±5.87y; 6 men), MCI patients (n=11; age 74.18±8.12y; schooling 7.55±4.32y; 5 men) and AD patients (n=25; age 76.16±4.96y; schooling 7.32±4.78y; 10 men) were submitted to neuropsychological assessment, S-TOFHLA and functional evaluation. Results: Differences on BD, Raven and Estimated IQ were found between controls and MCI patients as well as controls and AD patients. On the S-TOFHLA, differences were found between MCI and AD patients, controls and AD patients, but not between control and MCI groups. S-TOFHLA performance correlated strongly with schooling and all neuropsychological tests, except Clock Drawing. Conclusions: The S-TOFHLA seems to be a useful measure for determining the level of literacy in MCI patients, but not in AD patients. S-TOFHLA performance was more closely associated with neuropsychological test scores than were years of education and seems to be a good predictor of level of literacy. The Vocabulary subtest proved to be uninfluenced by the disease process in early stages and preserved in both MCI and AD patients, showing that semantic memory and crystallized intelligence are preserved.